Teaching of Geography in Uganda Secondary Schools: Reflections of Geography Teacher Trainees at the School of Education, Makerere University, Uganda - Kagoda, Alice Merab (Advances in Social Sciences Research Journal, 2016)
This paper examined the status of Geography Education in Secondary Schools of Uganda through the eyes of Geography teacher trainees. This study was based on a constructivist theory of learning. The teacher trainees with the guidance of the researcher were sent out to secondary schools in three Districts of Uganda. The eighty students in the class worked in groups of four each to carry out this study. Each group selected two schools, one well established with facilities and the other, a “third world” school which is rather deprived. The status of Geography in this study referred to the quality of teachers and students, availability of teaching materials, the teaching methods used by the in-service teachers, the learning environment, and use of technology, relevance of topics taught, availability of geography clubs and other learning activities. Results show that there is shortage of teaching materials, text books are outdated, teachers do not use interactive teaching methods, and some schools do not have qualified teachers and a general lack of well organized geography departments. They noted that well established schools with reasonable facilities are implementing the geography syllabus well and their performance in national examinations is good. Recommendations include; providing in-service courses, workshops, seminars to geography teachers in secondary schools, parents and government should work as a team to provide teaching/learning materials to schools. Schools to carry out career guidance to encourage students work hard and take their studies seriously.